2017
DOI: 10.21053/ceo.2016.00612
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Prognostic Factors in Malignant External Otitis

Abstract: Objectives Malignant external otitis (MEO) is a potentially fatal infection of the external auditory canal, temporal bone, and skull base. Despite treatment with modern antibiotics, MEO can lead to skull base osteomyelitis. Until now, there have been few studies on the prognostic factors of MEO.Methods We performed a retrospective study to identify prognostic factors of MEO, and a meta-analysis of other articles investigating MEO. On the basis of disease progression the 28 patients in our study were divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 23 publications
(30 reference statements)
2
60
0
4
Order By: Relevance
“…Despite advances in medical and surgical therapy, SBO has a mortality rate of 14.3%–22%. [1314] In a systematic review of 42 patients with central SBO, 31% had residual neurologic deficits after treatment. [12]…”
Section: Introductionmentioning
confidence: 99%
“…Despite advances in medical and surgical therapy, SBO has a mortality rate of 14.3%–22%. [1314] In a systematic review of 42 patients with central SBO, 31% had residual neurologic deficits after treatment. [12]…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Chen et al 15 reported that average glycemic levels among NOE patients were not associated with mortality in NOE patients. Also, Lee et al 13 reported that mean glucose levels were not statistically significant between controlled and uncontrolled NOE. In the presented study, mean glycemic levels during hospitalization were associated with DM duration (p=.005) and HbA1C levels (p-value 0.001), but were not associated with hospitalization duration or need for surgery.…”
Section: Discussionmentioning
confidence: 96%
“…Stern-Shavitet al 12 reported on patients from the same center and found that DM correlated and predicted disease specific mortality, however DM duration and severity were not analyzed. Leeet al 13 reported that DM duration was associated with uncontrolled NOE, but HbA1c was not associated with NOE progression. Similarly, Lohet al 7 reported that DM severity, defined by HbA1c >7.0% was not associated with the disease outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The overall mortality rates in MOE have been reported to be around 2.5%–15% in recent times ( Blyth et al., 2011 ; Das et al., 2019 ; Spielmann et al., 2013 ; Hatch et al., 2018 ). More than the surgical treatment and the time of initiation of therapy, the long duration of antibiotic treatment and the adequate control of underlying diabetes seem to be the best predictors of the favorable outcome in MOE ( Lee et al., 2017 ; Hatch et al., 2018 ; Khan et al., 2018 ). The reported duration of prolonged antibiotic therapy to completely eradicate the infection in MOE varies from three months to 11 months ( Conde-Diaz et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The reported duration of prolonged antibiotic therapy to completely eradicate the infection in MOE varies from three months to 11 months ( Conde-Diaz et al., 2017 ). During the course of prolonged antibiotic therapy the activity of disease can be monitored by the biochemical assay of acute phase reactants like ESR or C-reactive protein as well as by the radiological studies like gallium scan or single-photon emission -CT ( Lee et al., 2017 ; Conde-Diaz et al., 2017 ). However, follow up with repeated assay of ESR was not correlating with clinical improvement in our case and hence was not considered for treatment planning.…”
Section: Discussionmentioning
confidence: 99%